Acute Hyperglycemia Impairs Vascular Function in Healthy and Cardiometabolic Diseased Subjects: Systematic Review and Meta-Analysis - Loader, Jordan; Montero, David; Lorenzen, Christian; Watts, Rani; Méziat, Cindy; Reboul, Cyril; Stewart, Simon; Walther, Guillaume (Arteriosclerosis, thrombosis, and vascular biology, 2015)
OBJECTIVES—Controversy exists over the effect of acute hyperglycemia on vascular function. In this systematic review, we compared the effect of acute hyperglycemia on endothelial and vascular smooth muscle functions across healthy and cardiometabolic diseased subjects. APPROACH AND RESULTS—A systematic search of MEDLINE, EMBASE, and Web of Science from inception until July 2014 identified articles evaluating endothelial or vascular smooth muscle function during acute hyperglycemia and normoglycemia. Meta-analyses compared the standardized mean difference (SMD) in endothelial and vascular smooth muscle functions between acute hyperglycemia and normoglycemia. Subgroup analyses and metaregression identified sources of heterogeneity. Thirty-nine articles (525 healthy and 540 cardiometabolic subjects) were analyzed. Endothelial function was decreased (39 studies; n=1065; SMD, −1.25; 95% confidence interval, −1.52 to −0.98; P<0.01), whereas vascular smooth muscle function was preserved (6 studies; n=144; SMD, −0.07; 95% confidence interval, −0.30 to 0.16; P=0.55) during acute hyperglycemia compared with normoglycemia. Significant heterogeneity was detected among endothelial function studies (P<0.01). A subgroup analysis revealed that endothelial function was decreased in the macrocirculation (30 studies; n=884; SMD, −1.40; 95% confidence interval, −1.68 to −1.12; P<0.01) but not in the microcirculation (9 studies; n=181; SMD, −0.63; 95% confidence interval, −1.36 to 0.11; P=0.09). Similar results were observed according to health status. Macrovascular endothelial function was inversely associated with age, blood pressure, and low-density lipoprotein cholesterol and was positively associated with the postocclusion interval of vascular assessment. CONCLUSIONS—To our knowledge, this is the first systematic review and meta-analysis of its kind. In healthy and diseased subjects, we found evidence for macrovascular but not microvascular endothelial dysfunction during acute hyperglycemia.